ANALISIS PENGARUH LOCUS OF CONTROL DAN EMOTIONAL INTELLIGENCE TERHADAP KINERJA KARYAWAN DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT. TELKOM DIVRE JATENG DAN DIY) - Rilo Triatmojo, Galih; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2018)
This research aims to examine the impact of Locus of Control (LOC) and Emotional Intelligence (EI) to Employee Performance (JP) use Job Stress (JS) as intervening variable’s. The issues from this research are absence and late that impact to employee performance. This Research investigate two models use SPSS 23th version. First, influence of LOC and EI to JS. Second, influence of LOC, EI and JS to JP.Sample is a random of 105 person of PT Telkom Divre IV Jateng and DIY worker’s. Technique of sample collection used Accidental Sampling and use the analysis of Linear Analysis, Path Analysis and Sobel TestResearch result showed LOC and EI has a negative and significant correlation to JS. LOC and EI has a positive and significant correlation to JP. JS has a negative and significant correlation to JP.